Periodontal ageing and its management via pharmacological glucose modulation - Neves, Vitor C. M.; Savchenko, Viktor; Daly, James; Sharpe, Paul (Frontiers in Dental Medicine, 2024)
Periodontal disease (PD), a widespread non-communicable disease, affects over 90% of the global population with no known cure. Current management strategies focus on the stabilisation of disease progression, which is successfully achieved to a limited extent. Yet the never-ending battle between bacteria and the gingiva involves a complex interplay between genetic, microbial and environmental factors, demanding innovative approaches to improve the prevention and stabilisation of this disease. Glucose is the body's source of energy and research has shown that dysregulation of the glucose metabolism impacts PD establishment and progression, as well as the development of systemic non-communicable diseases. Metformin, a drug known for its efficacy in diabetes treatment via controlling glucose metabolism, also demonstrated cardioprotective effects, increased longevity, and anti-inflammatory properties. Metformin has been used in gel format in clinical trials for non-surgical treatment of PD, however, its systemic use in normoglycemic individuals with PD is less explored. A recent study presented compelling evidence of metformin's preventive potential, impacting PD and markers of systemic health involved in metabolic health linked to improvement of lifespan. Therefore, this review discusses the aspects of ageing as a concept in the periodontium and the potential benefits of modulating glucose metabolism through metformin to prevent PD, indirectly preventing systemic conditions involved in multi-morbidity, addressing a critical gap in current management. It also examines the choice between implementation of behaviour change and/or medication as a strategy to add to current oral hygiene strategies. Finally, it discusses the ethical implications of prescribing systemic medication in dentistry.